Taurine Attenuates Streptococcus uberis-Induced Bovine Mammary Epithelial Cells Inflammation via Phosphoinositides/Ca2+ Signaling - Li, Ming; Xi, Panpan; Xu, Yuanyuan; Wang, Zhenglei; Han, Xiangan; Ren, Wenkai; Phouthapane, Vanhnaseng; Miao, Jinfeng (Frontiers in Immunology, 2019)
Taurine may alleviate the inflammatory injury induced by Streptococcus uberis (S. uberis) infection by regulating intracellular Ca2+ levels. However, the underlying mechanisms remain unclear. Infection leads to subversion of phosphoinositides (PIs) which are closely related to Ca2+ signaling. In order to investigate whether taurine regulates inflammation by means of PIs/ Ca2+ systems, competitive inhibitors of taurine (β-alanine) siTauT, siPAT1, siPLC, siCaN, siPKC, and inhibitors of PLC (U73122), PKC (RO31-8220) and CaN (FK 506) were used. The results indicate that taurine transfers the extracellular nutrient signal for intercellular innate immunity to phosphoinositides without a need to enter the cytoplasm while regulating intracellular Ca2+ levels during inflammation. Both the Ca2+-PKCα-NF-κB and Ca2+-CaM-CaN-NFAT signaling pathways of S. uberis infection and the regulatory roles of taurine follow activation of PIs/Ca2+ systems. These data increase our understanding on the mechanisms of multifunctional nutrient, taurine attenuated inflammatory responses caused by S. uberis infection, and provides theoretical support for the prevention of this disease.